2016
DOI: 10.1371/journal.pone.0158782
|View full text |Cite
|
Sign up to set email alerts
|

To Invest or Not to Invest, That Is the Question: Analysis of Firm Behavior under Anticipated Shocks

Abstract: When companies are faced with an upcoming and expected economic shock some of them tend to react better than others. They adapt by initiating investments thus successfully weathering the storm, while others, even though they possess the same information set, fail to adopt the same business strategy and eventually succumb to the crisis. We use a unique setting of the recent financial crisis in Croatia as an exogenous shock that hit the country with a time lag, allowing the domestic firms to adapt. We perform a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…They found that it was mainly the older companies and those with a higher risk rating that demanded external finance more often, while the opposite was true for women-led businesses and businesses with positive profits. Kovac et al (2016) found higher survival rate for SMEs that invested prior to anticipated shock in comparison to similar SMEs that did not invest. They concluded that proper investment strategy might help the SMEs to adapt and survive external shocks such as the GFC.…”
Section: Introductionmentioning
confidence: 82%
“…They found that it was mainly the older companies and those with a higher risk rating that demanded external finance more often, while the opposite was true for women-led businesses and businesses with positive profits. Kovac et al (2016) found higher survival rate for SMEs that invested prior to anticipated shock in comparison to similar SMEs that did not invest. They concluded that proper investment strategy might help the SMEs to adapt and survive external shocks such as the GFC.…”
Section: Introductionmentioning
confidence: 82%
“…Given that prior studies find that micro firms tend to be particularly vulnerable to liquidity issues (i.e. Kovač et al, 2016;Perić and Vitezić, 2016) we investigate whether small creditors were particularly hard hit by these spillover effects.…”
Section: Research Strategymentioning
confidence: 99%
“…A parametric test was conducted to check if investors who made a prior investment before the recession were able to survive during this period. It turned out that there was around a 60-70% success rate for those who made investments (Kovac, Vukovic, Kleut, & Podobnik, 2016). This information is helpful to investors when they analyze if investing is wise when a recession is approaching.…”
Section: Probabilitymentioning
confidence: 99%